Reforming Pension System In Nepal - Paudel, Dilip Raj (Nepalese Journal of Insurance and Social Security, 2024)
Purpose: The pension system in Nepal is pivotal for safeguarding social security and financial stability among its aging populace, yet it grapples with substantial hurdles, encompassing demographic transformations, insufficient funding, and operational inefficiencies. The primary aim is to investigate and analyze different facets of Nepal’s pension system, assessing its adequacy, coverage, and sustainability. Design/Methodology/Approach: This study utilized a mixed-method approach, combining primary survey data from 237 respondents with secondary data from the Pension Management Office. Employing a descriptive research design, it aimed to offer insights into the current state of Nepal’s pension system and stakeholders’ perceptions. Findings: The findings revealed widespread dissatisfaction among respondents regarding the current provision of pension benefits, highlighting the urgent need for reforms. Key reform priorities identified included raising the retirement age, expanding coverage to the informal sector, increasing contribution rates, improving efficiency and management, and enhancing public awareness. Research limitation/ Implications: This study exclusively focused on the pension system, neglecting other components of social security benefits that many influence individuals’ motivation. Likewise, this study totally relied on descriptive analysis restricting its capacity to establish causal relationships. Likewise, this insight provides valuable guidance for policymakers in developing comprehensive reform strategies to address the systemic challenges and shortcomings in Nepal’s pension system, ensuring its long-term sustainability and adequacy for future retirees